Formation of Multiple‐Helical Core‐Shell Structure from Polyphenyl and Boron Nitride Nanotube. Issue 7 (31st May 2021) - Yang, Houbo; Zhang, Danhui; Liang, Ruquan; Liu, Zhongkui; Song, Yuanmei; Yang, Liu; Liu, Anmin
Abstract: In this manuscript, a multiple‐helical core‐shell structure is studied from polyphenyl and boron nitride nanotube (BNNT) through the molecular dynamics simulation. The results exhibited that polyphenyl is constrained in the inside of BNNT and self‐coiled to a helical configuration. In these systems, both the van der Waals potential well and the π–π stacking interaction between the polyphenyl and BNNT play a key role in the formation of helical nanostructures. The final configuration of composites can be influenced by many factors such as the diameter of BNNT, the chain number of polymer, the length of polymer, and the simulation temperature which are investigated in detail. This theory research about polyphenyl and BNNT may supply more theoretical foundation in chemical functionalization and helical polymer synthesis, which can be helpful for fabricating nanoscale devices. Abstract : The formation process of a multiple‐helical core‐shell structure is tracked by the molecular dynamics simulation. The simulation displays that polyphenyl is constrained in the inside of boron nitride nanotube and self‐coils to a helical configuration. The main driving forces in this whole process are van der Waals potential well and the π–π stacking interaction.